Dromia erythropus ... - In, First Published (Zenodo, 2022)
Dromia erythropus (Edwards in Catesby, 1771) (Figs. 5A–D, 6A–D) Cancer erythropus Edwards in Catesby, 1771: 37 [Type locality: unknown]. Dromia gouveai Melo & Campos Junior, 1999: 281, fig. 3A, B [Type locality: Jeribatuba, Itaparica Island, near Salvador, Bahia, Brazil]. Trindade and Martin Vaz specimens. 1 juvenile female (MZUSP 33351), Brazil, off Espírito Santo, Trindade Island, Enseada dos Portugueses, SECON, 20º30’20.9’’S, 29º18’43.7’’W, J.B. Mendonça coll., 29.iv.2014, 9.9 m. 1 juvenile male (MZUSP 33349), ibidem, Farol, 20º29’52.3’’S, 29º19’15.6’’W, J.B. Mendonça coll., 17.iv.2014, 13.3 m. 1 ovigerous female (MZUSP 42512), ibidem, 23.x.2014, 12.5 m. 1 megalopa (MZUSP 40354), ibidem, 22.iv.2014, 13.7 m. 1 juvenile female (MZUSP 40356), ibidem, Ponta da Calheta, 20º30’18.72’’S, 29º18’31.6’’W, J.B. Mendonça coll., 29.iv.2014, 15.9 m. 1 juvenile female (MZUSP 40360), ibidem, 25.vi.2015, 16.9 m. 1 juvenile male (MZUSP 40362), ibidem, Parcel das Tartarugas, 20º31’11.86’’S, 29º18’0.06’’W, J.B. Mendonça ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on pages 13-16, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...